Conformity, Social Norms and Tax Compliance - A.V. Demin (Психология и право, 2023)
The article analyzes the impact of social norms on tax compliance. The author defines social norms as standards of non-legal behavior that have been established in society and assimilated by an individual, which people follow due to the fact that they receive either greater inner satisfaction from actions that they consider correct, or because of approval from others. The author comes to the conclusion that conformity and evaluation by society are a powerful driver of decisions made by taxpayers. A person's social identity is an important factor of tax compliance. In this context, tax liabilities do not exist in a social vacuum. The social, cultural and institutional environment in which a taxpayer lives and works, his interactions with other people and organizations have a significant impact on tax compliance. Therefore, if a taxpayer is convinced that all (or most) people consider it the norm not to pay taxes, he is more likely to do the same. And, on the contrary, if a taxpayer is confident that others, as a rule, faithfully fulfill their tax obligations, they are more likely to comply with tax compliance.